2016
DOI: 10.1080/09540121.2016.1271103
|View full text |Cite
|
Sign up to set email alerts
|

Sexual identity and behavior in an online sample of Indian men who have sex with men

Abstract: Indian men who have sex with men are disproportionately impacted by HIV. While prevention efforts to date have focused on men who visit drop-in centers or physical cruising sites, little is known about men who are meeting sexual partners on virtual platforms. This paper explores issues related to sexual identity and sexual behaviors in an online sample of men who identified as gay (n=279) or bisexual (n=123). There were significant differences in outedness between the two groups, with 48% of bisexually-identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Prior national or multi-city samples of Indian MSM were recruited through physical venue-based approaches, and demonstrated similar or higher rates of HIV testing, ranging from 51–82%. 1,16 While the HIV testing prevalence we observed is comparable to smaller studies of Indian MSM recruited online, 5,6 prior studies have not examined correlates of HIV testing. Additionally, prior studies have not provided country-wide data needed to guide testing interventions for Indian MSM.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Prior national or multi-city samples of Indian MSM were recruited through physical venue-based approaches, and demonstrated similar or higher rates of HIV testing, ranging from 51–82%. 1,16 While the HIV testing prevalence we observed is comparable to smaller studies of Indian MSM recruited online, 5,6 prior studies have not examined correlates of HIV testing. Additionally, prior studies have not provided country-wide data needed to guide testing interventions for Indian MSM.…”
Section: Discussionsupporting
confidence: 59%
“…Though SNS disrupt traditional face-to-face outreach, SNS also provide access to hard-to-reach populations. Studies among SNS-using Indian MSM have found that up to 50% are unaware of their HIV status, 5,6 but were limited to small localities or did not examine correlates of HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…65 Two studies noted that bisexually identified men were less likely to be out as compared to gay men, and many of them passed as heterosexual. 43, 66…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study with sexual minority women found that isolation, anxiety, high substance use, and suicidal thoughts were common themes in these women's experiences. 35 Prevalence rates for depression, substance abuse and dependence, anxiety, and other psychiatric conditions from varied studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49] are described in Table 1. Badgett 25 stated that in the absence of studies providing a comparable estimate for non-LGBTQIA+ people in India, the population prevalence of a condition can be used as a benchmark.…”
Section: Prevalence Of Mental Health Conditionsmentioning
confidence: 99%
See 1 more Smart Citation